Monazite ID-TIMS U-Pb geochronology in the LAGIR laboratory, Rio de Janeiro State University: protocols and first applications to the assembly of Gondwana supercontinent in SE-Brazil - CARLA C.A. NETO; CLAUDIO M. VALERIANO; CLAUDIA R. PASSARELLI; MONICA HEILBRON; MARCELA LOBATO (Anais da Academia Brasileira de Ciências, 2014)
The chemical and spectrometric procedures of the U-Pb geochronology method on monazites, recently installed in the LAGIR laboratory, are described in detail. In addition, preliminary results on monazite samples from the Brasília and Ribeira belts are reported and discussed in the context of the regional geology. Several experiments for calibration of ion exchange chromatographic columns with the AG-1x8 resin, were performed with HCl, using dissolved natural monazite samples. The Pb blanks of reagents are ∼0.5 pg/g in acids and ∼1 pg/g in H2O. The total Pb blanks in chemical procedures were below 22 pg. Preliminary results are presented from three case studies related to Brasiliano orogenic belts of SE-Brazil, which correlate very well with previous age determinations from literature: two sub-concordant grains from an Araxá Group quartzite (southern Brasília belt) define a concordia age of 602.6 ±1.4 Ma; a -0.8% discordant grain from a quartzite of the São Fidelis Group (Costeiro Domain, central Ribeira belt) yielded a concordia age of 535.3 ± 2.4 Ma; two 0.4 % and 1.3 % discordant monazite grains from the post-collisional Itaoca Granite (Costeiro Domain, central Ribeira belt) define a concordia age of 476.4 ± 1.8 Ma.